Nanoparticles Dual Targeting Both Myeloma Cells and Cancer-Associated Fibroblasts Simultaneously to Improve Multiple Myeloma Treatment - Honglan Wang; Huiwen Liu; Chunyan Sun; Chunying Liu; Ting Jiang; Yanxue Yin; Aoshuang Xu; Zhiqing Pang; Bo Zhang; Yu Hu (MDPI AG, 2021)
Cancer-associated fibroblasts (CAFs) and myeloma cells could mutually drive myeloma progression, indicating that drug delivery to kill both CAFs and myeloma cells simultaneously could achieve better therapeutic benefits than to kill each cell type alone. Here, we designed a dual-targeting drug delivery system by conjugating paclitaxel (PTX)-loaded poly(ethylene glycol)-poly(lactic acid) nanoparticles (NPs) with a cyclic peptide (CNPs-PTX) with a special affinity with platelet-derived growth factor/platelet-derived growth factor receptor (PDGFR-β) overexpressed on both CAFs and myeloma cells. Cellular uptake experiments revealed that the cyclic peptide modification on CNPs could significantly enhance CNPs uptake by both CAFs and myeloma cells compared with unmodified NPs. Cytotoxicity tests showed that CNPs-PTX was more toxic to both CAFs and myeloma cells compared with its counterpart PTX-loaded conventional NPs (NPs-PTX). In vivo imaging and biodistribution experiments showed that CNPs could abundantly accumulate in tumors and were highly co-localized with CAFs and myeloma cells. The in vivo anti-tumor experiments confirmed that the anti-myeloma efficacy of CNPs-PTX was significantly stronger than that of NPs-PTX and free drugs. In summary, it is the first time that a dual-targeting strategy was utilized in the field of myeloma treatment through targeting both CAFs and myeloma cells simultaneously, which harbors a high potential of clinical translation for myeloma treatment.